HOW TO TEACH '˜LISTENING FOR LEARNING' IN A CLINICAL CONTEXT? - Junaid, Syed Muhammad; Usman Mahboob; Natasha Nadeem; Nayab lqbal; Ali Maqbool Khuwaja; Madeeha Bangash (Journal of Ayub Medical College Abbottabad, 2022)
Active listening skills are an important factor in communication skill set. And for budding doctors they need to be incorporated in the undergraduate medical programs. Studies have shown that patients, prefer the doctors who can listen to them instead of just looking at their signs and symptoms. Listening is related to empathy when strictly talking from patient's perspective. Having better listening skills can also lead to less prescription errors and help the doctor to identify some missing points from the history that can help in the diagnosis. Listening skills can be taught in different ways. Role plays are a safe way to teach them however, while teaching them in a clinical setting, we need to approach it in a different way like bedside teaching, Chairside Dental OPD etc.